Light as Stress Factor to Plant Roots – Case of Root Halotropism - Ken eYokawa; Ken eYokawa; Rossella eFasano; Tomoko eKagenishi; Frantisek eBaluska (Frontiers in Plant Science, 2014)
Despite growing underground, largely in darkness, roots emerge to be very sensitive to light. Recently, several important papers have been published which reveal that plant roots not only express all known light receptors but also that their growth, physiology and adaptive stress responses are light-sensitive. In Arabidopsis, illumination of roots speeds-up root growth via ROS-mediated and F-actin dependent process. On the other hand, keeping Arabidopsis roots in darkness alter F-actin distribution, polar localization of PIN proteins as well as polar transport of auxin. Several signaling components activated by phytohormones are overlapping with light-related signaling cascade. We also demonstrated that the sensitivity of roots to salinity is altered in the light-grown Arabidopsis roots. Particularly, light-exposed roots are less effective in their salt-avoidance behavior known as root halotropism. Here we discuss these new aspects of light-mediated root behavior from cellular, physiological and evolutionary perspectives.